Collagen-Based Tissue Engineering Strategies for Vascular Medicine - Copes, Francesco; Pien, Nele; Van Vlierberghe, Sandra; Boccafoschi, Francesca; Mantovani, Diego (Frontiers in Bioengineering and Biotechnology, 2019)
Cardiovascular diseases (CVDs) account for the 31% of total death per year, making them the first cause of death in the world. Atherosclerosis is at the roots of the most life-threatening CVDs. Vascular bypass/replacement surgery is the primary therapy for patients with atherosclerosis. The use of polymeric grafts for this application is still burden by high-rate failure, mostly caused by thrombosis and neointima hyperplasia at the implantation site. As a solution for these problems, the fast re-establishment of a functional endothelial cells (ECs) layer has been proposed, representing a strategy of crucial importance to reduce these adverse outcomes. Implants modifications using molecules and growth factors with the aim of speeding up the re-endothelialisation process has been proposed over the last years. Collagen, in virtue of several favourable properties, has been widely studied for its application in vascular grafts enrichment, mainly as a coating for vascular grafts luminal surface and as a drug delivery system for the release of pro-endothelialisation factors. Collagen coatings provide receptor-ligand binding sites for ECs on the graft surface and, at the same time, act as biological sealants, effectively reducing graft porosity. The development of collagen-based drug delivery systems, in which small molecule and protein-based drugs are immobilize within a collagen scaffold in order to control their release for biomedical applications, have been widely explored. These systems help in protecting the biological activity of the loaded molecules while slowing their diffusion from collagen scaffolds, providing optimal effects on the targeted vascular cells. Moreover, collagen-based vascular tissue engineering substitutes, despite not showing yet optimal mechanical properties for their use in the therapy, have shown a high potential as physiologically relevant models for the study of cardiovascular therapeutic drugs and diseases. In this review, the current state of the art about the use of collagen-based strategies, mainly as a coating material for the functionalization of vascular grafts luminal surface, as a drug delivery system for the release of pro-endothelialisation factors and as physiologically relevant in vitro vascular models and the future trend in this field of research will be presented and discussed.